ANALISA AREA GUDANG DENGAN METODE KAIZEN DI PT. INDAH PRAKASA SENTOSA TBK.CAB CILEGON - Hartadi Wijaya (Journal of Industrial Engineering & Management Research, 2023)
Problem when the company has many waste of time and costs at PT. Indah Prakasa Sentosa tbk. due to lack of attention to the layout goods in a warehouse regions , where many spares not lined up and unsuitable for use in the period 2021-2022 them ,cause just a heap time and money that could prejudice the Company. So, the study aims to get a job next efficiency by an effort to improve the quality of effectively by means of the concepts kaizen , 5s and (PDCA plan , doing , check , and action ). Result this study shows that the percentage for goods the difference is the lack of a record of workers of 57 % , The warehouse narrow is 19 % , lack of the availability of 14 % and the lowest distinction is it because of the landscape of dirty shed as many as 10 %